Evaluation of Athletic Events of Olympic History for 100 Years Using Ranking Algorithm - Lalitha, C; Arulselvarani, S (International Journal of Computer Sciences and Engineering, 2025)
This paper investigates the result of athletic games of Olympic history for the past 100 years. As a case study, we evaluate ZeroR classification machine algorithms on game datasets. Here we compare the dataset in ranking algorithms in order to determine the results like leading city and the winner of the game. In this paper, we used machine learning data mining tool WEKA for different analysis. We have provided an evaluation based on applying these classification methods on our datasets and measuring the accuracy of test results.